The Progress of the SDGs Research - Wignyo Adiyoso (Pusbindiklatren Bappenas, 2022)
The global Sustainable Development Goals (SDGs) provide an evidence-based policy for sustainable development planning and programming to halt poverty, gain prosperity and protect the planet by 2030. The SDGs consist of 17 goals and 169 targets that emphasize the balance between economic, social and environmental sustainability. Since the framework launched in 2015, there is growing international policies, practices, innovations, assessments and research activities related to such issues